2015
DOI: 10.4103/2231-4040.154526
|View full text |Cite
|
Sign up to set email alerts
|

The magic of magic bugs in oral cavity: Probiotics

Abstract: The aim of this review is to present an update about the current status of probiotics in the field of dentistry. Oral infections are the most common forms of infections. It is necessary to understand the role of the ecology and microbiology of the oral cavity in better understanding of the pathogenesis of various oral diseases. The concept of bacteriotherapy has been an emerging field in dentistry. The use of health-beneficial micro-organisms to heal diseases or support immune function was first introduced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…While human and animal studies have established the ability to successfully populate the oral cavity or gastrointestinal tract with specific strains, combinations of bacteria, or bacteria genetically modified to produce enzymes or metabolites[74,404407], it is by no means clear that repopulation by probiotic bacteria must occur to achieve its intended effects[309,407]. Given, however, that probiotic therapy exerts a beneficial effect on dental caries, periodontitis, and pharyngitis in the oral cavity[408411], as well as on obesity, hypertension, insulin resistance, and heart failure via the gut(reviewed:[399,403]), there is clear potential to treat PH with microbial interventions by modifying either oral or gastrointestinal bacteria.…”
Section: Therapeutic Strategies To Target the Enterosalivary Pathway:mentioning
confidence: 99%
“…While human and animal studies have established the ability to successfully populate the oral cavity or gastrointestinal tract with specific strains, combinations of bacteria, or bacteria genetically modified to produce enzymes or metabolites[74,404407], it is by no means clear that repopulation by probiotic bacteria must occur to achieve its intended effects[309,407]. Given, however, that probiotic therapy exerts a beneficial effect on dental caries, periodontitis, and pharyngitis in the oral cavity[408411], as well as on obesity, hypertension, insulin resistance, and heart failure via the gut(reviewed:[399,403]), there is clear potential to treat PH with microbial interventions by modifying either oral or gastrointestinal bacteria.…”
Section: Therapeutic Strategies To Target the Enterosalivary Pathway:mentioning
confidence: 99%
“…Also poor daily oral hygiene may increase the chronic inflammatory burden to the body [ 16 ]. According to accumulating data from clinical trials, probiotics have shown capacity to be an alternative strategy for the prevention and treatment of bacterial/yeast diseases [ 17 , 18 ]. In the past decade, researchers have investigated the antagonistic interactions between probiotics and pathogens in their planktonic form in broth media and/or in colonies on agars [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Cases 1 and 2, it is expected that, through such processes, modulation of the oral–biofilm composition will take place [ 33 , 34 , 35 , 36 ]. This would result in reducing the pathogenicity and cariogenic potential of biofilm microorganisms [ 33 , 37 , 38 , 39 ] as well as reducing the potential pathogens burden in oral biofilm [ 39 , 40 , 41 ]. The final outcome will definitely present a clear path for caries, gingivitis and periodontal management [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Possible Roles Of Probiotics In the Oral Cavitymentioning
confidence: 99%